Relationship between self-efficacy and organizational commitment among substance abuse counsellors of methadone maintenance therapy - Mariapah, Sinthumathi; Ahmad, Jamaludin; Wan Jaafar, Wan Marzuki (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
In Malaysia, Methadone Maintenance Therapy (MMT) is a harm-reduction strategy program and methadone is known as corrective therapy in Malaysia (Wickersham, et as., 2012; Mohamed, et al, 2010). The counsellors have a big role to provide the counselling and information related to treatment of MMT. Therefore, it is necessary for a counsellor in MMT to have high self-efficacy and is committed to the organization they are working. The study focuses on the assimilation of the counsellors’ self-efficacy and organizational commitment of MMT in Malaysia. Hence the main objective is to study the relationship between the self-efficacy and organizational commitment of Methadone Maintenance Therapy in Malaysia. This research is a quantitative research.